2022
DOI: 10.1186/s13000-022-01202-x
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of next-generation sequencing and fragment analysis for the detection and allelic ratio determination of FLT3 internal tandem duplication

Abstract: Background Currently, FLT3 internal tandem duplication (ITD) is tested by fragment analysis. With next-generation sequencing (NGS), however, not only FLT3 ITD but also other mutations can be detected, which can provide more genetic information on disease. Methods We retrospectively reviewed the results of two tests—fragment analysis and a custom-designed, hybridization capture-based, targeted NGS panel—performed simultaneously. We used the Pindel a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…36 With the development of the new bioinformatics analysis, the hybridization capture-based NGS achieved 99.6% coincidence rate with fragment analysis for FLT3-ITD follow up. 37 In this study we demonstrated that NRAS was the most com- This panel was able to detect more positive patients with less cost.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…36 With the development of the new bioinformatics analysis, the hybridization capture-based NGS achieved 99.6% coincidence rate with fragment analysis for FLT3-ITD follow up. 37 In this study we demonstrated that NRAS was the most com- This panel was able to detect more positive patients with less cost.…”
Section: Discussionmentioning
confidence: 67%
“…However, patient‐specific primers have to be designed from the tumor samples 36 . With the development of the new bioinformatics analysis, the hybridization capture‐based NGS achieved 99.6% coincidence rate with fragment analysis for FLT3‐ ITD follow up 37 …”
Section: Discussionmentioning
confidence: 99%
“…Due to the limitations of existing microbiological detection methods (low culture sensitivity, long time required; limited number of microorganisms detected by serology and polymerase chain reaction), its diagnosis is still challenging. [ 4 , 5 ] In addition, the lungs are not aseptic and there are microbial colonies in both healthy and diseased conditions. How to distinguish pathogens from colonized bacteria is the main challenge in pathogen diagnosis of LRTI.…”
Section: Introductionmentioning
confidence: 99%
“…Novel bioinformatic analysis is required to bridge this clinical gap, improve the sensitivity and accuracy of ITD characterization, [23][24][25][26] as well as accurately calculate the allele ratio. 21,22,27,28 In the published studies, 13,21,22 multiple steps and tools are usually needed to create a final report of FLT3-ITD. An NGS assay using the Archer ® VariantPlex ® Myeloid panel, coupled with the proprietary Archer ® Analysis pipeline (ArcherDX, Inc., Boulder, CO), is a highly sensitive assay for detecting FLT3-ITD, especially for intermediate to long ITDs, compared to traditional PCR-based fragment length analysis (Ding and Zhang, unpublished clinical validation data).…”
Section: Introductionmentioning
confidence: 99%
“…However, it is a well‐known challenge that insertion mutations over 25 bp length are difficult to analyze and many times being missed by most bioinformatic pipelines. Novel bioinformatic analysis is required to bridge this clinical gap, improve the sensitivity and accuracy of ITD characterization, 23–26 as well as accurately calculate the allele ratio 21,22,27,28 . In the published studies, 13,21,22 multiple steps and tools are usually needed to create a final report of FLT3 ‐ITD.…”
Section: Introductionmentioning
confidence: 99%